Faktor determinan financial distress pada industri manufaktur tahun 2020-2023 - Shanti, Putrina Nila; Widjaja, Indra (Jurnal Manajemen Bisnis dan Kewirausahaan, 2025)
This study aims to examine the effect of Good Corporate Governance (GCG) mechanisms and financial performance on the likelihood of financial distress in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period, which coincides with the ongoing economic disruptions caused by the COVID-19 pandemic. The study employs four independent variables: the proportion of independent commissioners, board of directors’ size, ownership concentration, and financial performance measured by Return on Assets (ROA). Financial distress is assessed using the Altman Z-Score model. A total of 46 manufacturing companies were selected through purposive sampling, and the data were analysed using logistic regression. The findings indicate that both the proportion of independent commissioners and ROA have a significant positive effect on financial distress, while board size has positive effect but not significant. Ownership concentration does not have a significant effect. These results highlight the importance of strengthening independent oversight and enhancing operational efficiency to mitigate financial distress during periods of economic turbulence. The novelty of this study lies in its focus on the COVID-19 crisis years, providing empirical insights into corporate resilience and governance effectiveness under global emergency conditions. This study aims to examine the effect of Good Corporate Governance (GCG) mechanisms and financial performance on the likelihood of financial distress in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period, which coincides with the ongoing economic disruptions caused by the COVID-19 pandemic. The study employs four independent variables: the proportion of independent commissioners, board of directors’ size, ownership concentration, and financial performance measured by Return on Assets (ROA). Financial distress is assessed using the Altman Z-Score model. A total of 46 manufacturing companies were selected through purposive sampling, and the data were analysed using logistic regression. The findings indicate that both the proportion of independent commissioners and ROA have a significant positive effect on financial distress, while board size has positive effect but not significant. Ownership concentration does not have a significant effect. These results highlight the importance of strengthening independent oversight and enhancing operational efficiency to mitigate financial distress during periods of economic turbulence. The novelty of this study lies in its focus on the COVID-19 crisis years, providing empirical insights into corporate resilience and governance effectiveness under global emergency conditions.